2004
DOI: 10.1111/j.1365-2249.2004.02437.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of partial or total thymectomy during open heart surgery in infants on the immune function later in life

Abstract: SUMMARYInfants undergoing open heart surgery often have all or part of their thymus removed. The activity of the immune system has not been investigated thoroughly in these children, and only shortly after the operation. Therefore, it was decided to investigate the activity of the immune system in more detail in children several years after their operation. Peripheral blood samples from 19 children who had undergone open heart surgery during their first months of life was collected (study group) and from 19 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 13 publications
6
88
1
Order By: Relevance
“…Previous short-term surveys showed that thymectomized children have reduced CD4 + T cell and TCR excision circle numbers compared with age-matched controls (6)(7)(8)(9)(10). More recently, reduction of naive CD4 + T cell numbers and production in thymectomized patients was shown to correlate with chronological age and time since thymectomy (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous short-term surveys showed that thymectomized children have reduced CD4 + T cell and TCR excision circle numbers compared with age-matched controls (6)(7)(8)(9)(10). More recently, reduction of naive CD4 + T cell numbers and production in thymectomized patients was shown to correlate with chronological age and time since thymectomy (11).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of PBMC samples from YATECs, taken an average of 2 decades after thymectomy, revealed clear alterations in the CD4 + T cell compartment (as expected from previous studies on CHD patients; ref. [6][7][8][9][10][11] as well as in the CD8 + T cell compartment. We found decreased CD4 + and CD8 + T cell counts in YATECs compared with age-matched controls, and even compared with middle-aged adult controls (Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of postsurgical immunodeficiency, recurrent infections, neoplasm, or autoimmune reactions was also not significantly related with thymectomy procedures. 32,34,35 This occurrence might be explain by an incomplete thymectomy, release of mature T cells before the procedure, compensatory increase in the nonspecific immune responses such as neutrophils and natural killer cells, and activation of other reticuloendothelial cells. 34 Failure to thrive and poor nutritional status have been considered as one of the major problems in children with congenital cardiac anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, even species presumed to follow similar immune system development can have different responses to immunotoxicants. Removal of the human thymus at birth (due to cardiac transplantation) does not result in autoimmunity or abnormal immune function in children evaluated up to 16 years post-transplantation (Eysteindottir et al, 2004). Hence, the rat may be more predictive of the outcome of neonatal thymectomy in humans than the mouse, but why this is the case is unknown.…”
Section: Impact On Interpreting Differential Findings Across Non-clinmentioning
confidence: 99%